Insight into Management Issues modeling for Perfect Business Simulation - Sadique Shaikh; Rajkumar Kankariya (Journal of Model Based Research, 2019)
In this paper, I try to focus on widely growing field of Management Science; and that, “Modeling of Management Issues “. Now days Business Simulation techniques are used to earn more profit from Business and this is only issues control future course of actions properly. By using models we can predict & control future course of action & situation. Modeling is not a new subject. It’s oldest technique, but widely used in Physical Sciences, like Chemistry, Physics, Electronics, Engineering field, But it’s again become vital after some time in Life Sciences, like Botany, Zoology, Bio-Chemistry, Bio-Tech and Medical field problem modeling and now in current world it’s also become very vital in Information Technology and Management subjects. Here one question is always arise, why such a modeling is needed, and where and when needed, and answer of this simple question is, considering some simple problems like ‘ to find out the width of a river (But your are not allowed to cross it), find out the temperature (but you are not allowed to use thermometer), means try to find out any Quantity or parameter/variable without existence or entity of that, and if virtual situation satisfied by using modeling technique, we implement that virtual model for actual situation. In last I want to conclude modeling is the heart of any branch of Education, weather its science, Arts, Commerce, Medical, Information Technology, Engineering or Management and in summaries form I want to say this paper is nothing but one of the theoretical model, which is for modeling of Management issues for perfect Business Simulation.
Keywords: Business Simulation